Electroacupuncture and human iPSC-derived small extracellular vesicles regulate the gut microbiota in ischemic stroke via the brain-gut axis - Zhang, Qiongqiong; Deng, Peiying; Chen, Suhui; Xu, Hong; Zhang, Yamin; Chen, Hui; Zhang, Jianmin; Sun, Hua (Frontiers in Immunology, 2023)
Electroacupuncture (EA) and induced pluripotent stem cell (iPSC)-derived small extracellular vesicles (iPSC-EVs) have substantial beneficial effects on ischemic stroke. However, the detailed mechanisms remain unclear. Here, we explored the mechanisms underlying the regulation of EA and iPSC-EVs in the microbiome-gut-brain axis (MGBA) after ischemic stroke. Ischemic stroke mice (C57BL/6) were subjected to middle cerebral artery occlusion (MCAO) or Sham surgery. EA and iPSC-EVs treatments significantly improved neurological function and neuronal and intestinal tract injury, downregulated the levels of IL-17 expression and upregulated IL-10 levels in brain and colon tissue after cerebral ischemia−reperfusion. EA and iPSC-EVs treatments also modulated the microbiota composition and diversity as well as the differential distribution of species in the intestines of the mice after cerebral ischemia−reperfusion. Our results demonstrated that EA and iPSC-EVs treatments regulated intestinal immunity through MGBA regulation of intestinal microbes, reducing brain and colon damage following cerebral ischemia and positively impacting the outcomes of ischemic stroke. Our findings provide new insights into the application of EA combined with iPSC-EVs as a treatment for ischemic stroke.